2010
DOI: 10.4319/lo.2010.55.4.1668
|View full text |Cite
|
Sign up to set email alerts
|

The Mekong River plume fuels nitrogen fixation and determines phytoplankton species distribution in the South China Sea during low and high discharge season

Abstract: The influence of the Mekong River (South China Sea) on N 2 fixation and phytoplankton distribution was investigated during the lowest-and highest-discharge seasons (April 2007 and September 2008, respectively). The river plays an essential role in providing nutrients (nitrate, phosphate, silicate) for the adjacent sea and creates different salinity and nutrient gradients over different seasons. River water (salinity 0), mesohaline waters (salinity 14-32), a transition zone with salinities between 32 and 33.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 41 publications
7
77
1
1
Order By: Relevance
“…This would have important consequences on the sediment deposition in the delta that seems to have already shifted from a net depositional (accretion) regime into a net erosion regime (Anthony et al, 2015;Liu et al, 2017). The nutrient inputs to the continental shelf from the Mekong delta sustain high phytoplankton growth in the Mekong River plume (Grosse et al, 2010), which is one the most productive areas of the South China Sea (Liu et al, 2002;Qiu et al, 2011;Gao et al, 2013;Loisel et al, 2017).…”
Section: Description Of the Mekong River And Deltamentioning
confidence: 99%
“…This would have important consequences on the sediment deposition in the delta that seems to have already shifted from a net depositional (accretion) regime into a net erosion regime (Anthony et al, 2015;Liu et al, 2017). The nutrient inputs to the continental shelf from the Mekong delta sustain high phytoplankton growth in the Mekong River plume (Grosse et al, 2010), which is one the most productive areas of the South China Sea (Liu et al, 2002;Qiu et al, 2011;Gao et al, 2013;Loisel et al, 2017).…”
Section: Description Of the Mekong River And Deltamentioning
confidence: 99%
“…In particular, since breaking the triple bond N 2 molecule is energetically expensive, it has been assumed that if N in the form of NO − 3 and/or NH + 4 is present, the assimilation of these forms of N will be used before N 2 fixation occurs (Falkowski, 1983;Karl et al, 2002). However, our understanding of marine nitrogen fixation is constantly evolving and increasing numbers of field studies report the presence of nitrogen fixation and/or active diazotrophs in a wide range of N-rich ecosystems, including relatively high latitudes (Needoba et al, 2007), nutrient enriched estuarine and coastal waters (Short and Zehr, 2007;Rees et al, 2009;Grosse et al, 2010;Bombar et al, 2011), upwelling area (Moutin et al, 2008), eddies (Church et al, 2009) and even High Nutrient, Low Chlorophyll waters (Bonnet et al, 2009). In particular, N 2 fixation seems to be particularly favoured as soon as N:P ratios drop below 16:1, even if nitrate concentrations are high, like above large OMZs" (e.g.…”
Section: Western Mediterranean Sea (Station B To a Tomentioning
confidence: 99%
“…However, the discovery of a large diversity of organisms able to fix N 2 , and their wide distribution, indicated that BNF may be more widespread than previously thought (Moisander et al, 2010). Recent studies demonstrate the presence and activity of diazotrophs in DIN-enriched environments such as the eastern tropical North Atlantic (Voss et al, 2004), the western English Channel (Rees et al, 2009), the Mekong River plume in the South China Sea (Grosse et al, 2010), the temperate NE American coast (Mulholland et al, 2012), and mesohaline temperate estuaries between the Baltic Sea and the North Sea (Bentzon-Tilia et al, 2015). Evidences of BNF have also been reported in upwelling systems such as the eastern equatorial Atlantic (Voss et al, 2004;Foster et al, 2009;Subramaniam et al, 2013), the Benguela upwelling system (Sohm et al, 2011;Benavides et al, 2014), and the region off central Chile (Raimbault and Garcia, 2008;.…”
Section: Introductionmentioning
confidence: 99%